Pengaruh Return Saham Terhadap Kepemilikan Institusional Sebagai Variabel Moderating Pada Perusahaan Manufaktur Terdaftar Di BEI - Noviza Asni Waruwu (Journal Research of Economic and Bussiness, 2022)
The study aims to examine the influence of return on assets, operating cash flow, financing cash flow, investment cash flow, economic value added, residual income, market value added, debt to equity ratio, to return stock with institusional ownership as a moderating variable. The population in this study is a manufacturing company in Indonesia Stock Exchange period of 2015 – 2019. By using purposive sampling method, the sample number 52 manufacturing company with 208 observations. By using multiple regression analysis, the results showed simultaneously or synchronously (test F) return on assets, operating cash flow, financing cash flow, investment cash flow, eonomic value added, residual income, market value added, debt to equity ratio positive and significant effect on return stock. Partially return on assets and cash flow funding positive and significant impact on the return of shares, while operating cash flow, investment cash flow, economic value added, residual income, market value added, and debt to equity ratio has no significant effect on return stock. Test results residual indicate that institusional ownership is not able to moderate the influence of return on assets, operating cash flow, financing cash flow, investment cash flow, economic value added, residual income, market value added, and debt to equity ratio on return stock to manufacturing company in Indonesia Stock Excahnge 2015 – 2019.